Assessment of molecular and clinical characteristics in blood transfusion dependent HbE/β-thalassemia patients - Islam, Nazneen Naher; Hossain, Mohabbat; Das, Shuvo Chandra; Seuti, Sabrina Alam; Chowdhury, Mahmood A (Jahangirnagar University Journal of Biological Sciences, 2021)
Hb E/β-thalassemia is one of the most common forms of hemoglobinopathies worldwide. This life-threatening genetic disorder is not completely curable. This study aims to investigate the correlation of mutations with clinical manifestations among the transfusion dependent Hb E/β- thalassemia patients using molecular, hematological and biochemical methods. A total of 60 blood samples were collected from regular blood transfusion-dependent HbE/β-thalassemia patients. Mutations within HBB gene were analysed by Sanger sequencing, BLAST 2.0, HbVar database and Alibaba 2.1. Clinical data were analysed based on CBC, Hemoglobin Electrophoresis and Serum Ferritin assay. Results demonstrate that a total of three mutationsdeletion of A (+23bp in HBB promoter region), c.9 T>C and c.79 G>A were detected among the study population, where deletion of A (+23bp in HBB promoter region) is a novel mutation. A total of three (USF, AP-1 and GATA-1) important putative binding sites were identified within the mutated region of HBB gene. Hematological analysis also showed remarkable correlation between the mutations and clinical manifestations in the patients. Reduced levels of RBC, Hb, MCV and MCH were found among the patients than the normal. Highly increased level of serum ferritin was also found among the patients due to the frequent destruction of RBCs. In conclusion, the findings of this study will be helpful to understand the mutational and hematological status of HbE/β-thalassemia patients. And this study will also be beneficial for effective molecular drug designing, drug response and other therapeutic approach for HbE/β-thalassemia patients. Jahangirnagar University J. Biol. Sci. 9(1 & 2): 109-121, 2020 (June & December)